SIMULATION OF AN ELECTRIC VEHICLE FIRE ON A RO-RO FERRY - Pitana, Trika; Kevin Y. H. Soewirjo, Mikha; Siswantoro, Nurhadi; Nurwahyudy, Aleik (Journal of Applied Engineering Science, 2025)
With the increasing demand for electric vehicles (EVs), the maritime transportation of these vehicles has become commonplace. Nevertheless, transporting EVs via car carriers presents a potential fire hazard. Data from the National Transportation Safety Board (NTSB) indicates that in 2020, 52 recorded fires involving EVs in the United States. These fires may be attributed to various factors, including battery malfunctions, overcharging, and damage sustained during transit. Once ignited, these fires can spread rapidly due to the proximity of the vehicles and the limited firefighting resources available on board. Numerous fire incidents involving car carriers transporting EVs have prompted safety concerns and underscored the necessity for enhanced regulations and safety protocols in recent years. According to the National Transportation Safety Committee (NTSC), Indonesia has reported 34 fires on vessels from vehicle incidents since 2007. Consequently, this research aims to mitigate damage and ascertain whether existing extinguishing systems effectively extinguish EV fires or if new recommendations are warranted. This study employs the Fire Dynamic Simulator (FDS) program to simulate fire behaviour, smoke propagation, and extinguishing. The findings highlight the importance of reducing fire temperatures to below 70°C within 400 to 500 s, particularly in the recommended scenario 2, which involves utilizing dedicated EV confined spaces. Ultimately, this approach minimizes smoke dispersal and emphasizes the necessity of lower temperatures for effective firefighting measures and reducing damage severity.